Extracellular Vesicles-mediated recombinant IL-10 protects against ascending infection-associated preterm birth by reducing fetal inflammatory response - Kammala, Ananth Kumar; Mosebarger, Angela; Radnaa, Enkhtuya; Rowlinson, Emma; Vora, Natasha; Fortunato, Stephen J.; Sharma, Surendra; Safarzadeh, Melody; Menon, Ramkumar (Frontiers in Immunology, 2023)
barriers to delay E. coli-induced PTB to deliver live pups at term. Delay in PTB was associated with reduced feto-maternal uterine inflammation (immune cell infiltration and histologic chorioamnionitis, NF-κB activation, and proinflammatory cytokine production).CONCLUSIONS: eIL-10 administration was safe, stable, specific, delayed PTB by over 72 hrs and delivered live pups. The delivery of drugs using EVs overcomes the limitations of in-utero fetal interventions. Protecting IL-10 in EVs eliminates the need for the amniotic administration of recombinant IL-10 for its efficacy.